2020
DOI: 10.3390/polym12051167
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Engineering of Advanced Polymeric Materials—Part VII: Degradation of Biopolymer Welded Joints

Abstract: Welding technology may be considered as a promising processing method for the formation of packaging products from biopolymers. However, the welding processes used can change the properties of the polymer materials, especially in the region of the weld. In this contribution, the impact of the welding process on the structure and properties of biopolymer welds and their ability to undergo hydrolytic degradation will be discussed. Samples for the study were made from polylactide (PLA) and poly(3-hydroxyalkanoate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…At treatment temperatures of 140–150°C, PLA remains amorphous, and seal temperatures are only slightly elevated, compared to untreated PLA 120 . Finally, it is shown that the chemical structure and molar mass of PLA, before and after conductive heating, are not changed, based on nuclear magnetic resonance spectra and gel permeation chromatography 121 …”
Section: Polyestersmentioning
confidence: 93%
See 1 more Smart Citation
“…At treatment temperatures of 140–150°C, PLA remains amorphous, and seal temperatures are only slightly elevated, compared to untreated PLA 120 . Finally, it is shown that the chemical structure and molar mass of PLA, before and after conductive heating, are not changed, based on nuclear magnetic resonance spectra and gel permeation chromatography 121 …”
Section: Polyestersmentioning
confidence: 93%
“…Sealed films with poly(3‐hydroxybutyrate‐co‐4‐hydroxybutyrate) are used in a shelf life study, but no information is shared on the seal performance and settings 134 . Another study evaluates chemical structure and molar mass of PHBV, before and after conductive heating, but has not found any changes 121 …”
Section: Polyestersmentioning
confidence: 99%
“…Thermal transitions of patterns were analyzed by differential scanning calorimetry (DSC) under nitrogen flow using a TA-DSC Q2000 apparatus (TA Instruments, Newcastle, DE, USA) from 20 to 200 °C at a heating rate of 20 °C/min. 38 2.3.6. Antimicrobial Activity.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, polymer nanocomposites containing nanoparticles of metals such as silver, copper and zinc oxide have attracted the most attention due to their pronounced pharmacological effects, including antimicrobial, antiviral, anti-inflammatory, immunomodulatory, and high stability in extreme conditions [5][6][7][8][9]. A promising polymer for the creation of antimicrobial and antiviral silver-containing nanocomposites is polylactide (PLA), which has significant advantages over other polymers, namely it is thermoplastic and is characterized by high mechanical strength, biocompatibility and non-toxicity [10,11]. These benefits allow the use of PLAs for biomedical packaging, food packaging, and 3D printing technology.…”
Section: Introductionmentioning
confidence: 99%